BEHAVIORAL GENETICS AND PERSONALITY: THE POSSIBLE APPROACH TO UNDERSTANDING THE ETIOLOGY OF INDIVIDUAL DIFFERENCES - Bratko, Denis (Array, 2007)
The paper presents the theoretical basis of behavioral genetics methods, as well as the empirical evidence regarding individual differences in personality traits. The question whether and how much genetic and environmental factors affect personality is one of the possible approaches to our understanding of individual differences. Behavioral genetic studies indicate that both genetics and environment contribute to the development of individual differences in personality. The review of twin, family, adoption, and molecular genetic studies of individual differences in personality traits is presented. Twin studies indicate that genetic factors explain roughly 40-60% of the population variance in personality traits. On the other hand, family and adoption studies consistently show lower heritability of personality variables. Methods of molecular genetics which are used in analysis of behavioral phenotypes are also presented. As an example of these methods, studies of relation between novelty seeking and DRD4 gene are presented, as well as the molecular genetic findings about the interaction of genes and environment.